2018
DOI: 10.21608/ajas.1999.16654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preharvest Application of ProTone, Methionine and Oleic acid as Alternative Materials to Ethephon for Enhancing Berry Coloration and Quality of "Flame Seedless" Table Grapes

Abstract: In this experiment, ten-years-old "Flame Seedless" grapevines at El-Nubaria region, Behira governorate, Egypt, were preharvest sprayed during 2016 and 2017 seasons with water only with surfactant (control), 400 mg/ L ethephon, 100 mg/ L ProTone (active ingredient of Abscisic acid 10%), 100 mg / L methionine, 400 mg/ L oleic acid, ProTone plus methionine, ProTone plus oleic acid and ProTone plus methionine and oleic acid, in order to investigate their influence on berry coloration, berry quality of grapes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…On the contrary, many studied mentioned that thiourea enhanced chlorophyll content. Meanwhile, foliar spray of methionine increased total chlorophyll contents of okra ( Zulqadar et al, 2015) and Attia (2018) on grapes. It could be refer to that thiourea and methionine could need more time to induce effect on leaf chlorophyll content and/or it thiourea and methionine degradation by plant after spraying direct and /or other factors make plant not ready to response to give effect on leaf chlorophyll content.…”
Section: Leaf Total Chlorophyll Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, many studied mentioned that thiourea enhanced chlorophyll content. Meanwhile, foliar spray of methionine increased total chlorophyll contents of okra ( Zulqadar et al, 2015) and Attia (2018) on grapes. It could be refer to that thiourea and methionine could need more time to induce effect on leaf chlorophyll content and/or it thiourea and methionine degradation by plant after spraying direct and /or other factors make plant not ready to response to give effect on leaf chlorophyll content.…”
Section: Leaf Total Chlorophyll Contentmentioning
confidence: 99%
“…In addition, foliar spray of methionine increased the of flowers and number of fruits of okra ( Zulqadar et al, 2015) and Attia (2018) on grapes.…”
Section: Fruit Set Percentagementioning
confidence: 99%
See 1 more Smart Citation
“…In juice of berries, total soluble solids (TSS) were determined according to hand refractometer, juice acidity as tartaric acid was determined according to AOAC, (1985) and skin berry anthocyanin content (mg/100g) was determined according to Fuleki and Francis (1968). To assess berry weight loss and berry shatter percentage after storage on room temperature (20± 2°C) for three days, another two bunches were used from each replication according to the methods mentioned by Attia, (2018). The experiment was arranged in a completely randomized block design (RCBD) and seven treatments were used (7 treatments with three replication).…”
Section: -Years-old "Kingmentioning
confidence: 99%
“…Various studies have suggested that the exogenous application of abscisic acid (ABA) increases the anthocyanin content of the skins of table grape cultivars, without changing berry maturation and without causing excessive softening (Lee et al, 1997;Cantín et al, 2007;Peppi et al, 2006. Attia (2018) recommended that using the ABA (Protone) plus methionine and oleic acid at veraison stage as an alternative to Ethrel (ethephon) treatment to overcome some adverse effects of Ethrel such as increased berry shattering and berry weight loss, which reflects on berry appearance.…”
Section: Introductionmentioning
confidence: 99%